PEMANFAATAN SISTEM INFORMASI KOPERASI DALAM MENINGKATKAN KEPERCAYAAN DAN LOYALITAS MASYARAKAT KOPERASI LEMBAGA KEUANGAN MIKRO AGRIBISNIS ( LKM A ) BERKAH MLATI MULYO PETEAN KENDAL - Eko Riyanto; Agus Alwi Mashuri; Mahmudi Mahmudi (LPPM Universitas Bina Bangsa, 2024)
The benefits of the LKMA Cooperative are felt by the local community because with this cooperative farmers can continue to produce their agricultural land without fear of lack of capital. Currently, the number of members has reached 105 customers, where transactions have reached 180,000,000. This makes both administrative and financial processes very important in serving members. Currently, the bookkeeping carried out by cooperatives is computer-based using Microsoft Excel, but it is not yet efficient because cooperative administrators can only carry out transactions at certain times, such as monthly meetings, which results in long and time-consuming transaction process queues. Apart from that, the recording process still uses a card which is proof that the customer has paid the instalments, but manual recording has many weaknesses, including being left behind, damaged and even lost. Under current conditions, technology is needed to help cooperative administrators manage their cooperatives effectively and efficiently. The STMIK Himsya Semarang community service team saw an opportunity to assist LKMA cooperative administrators in managing cooperative finances using Cooperative Information System technology. This web-based cooperative information system application is made easier both from the admin and customer side because it uses the internet which can be accessed anytime and anywhere. All transactions carried out will be recorded in the database and can be seen in real-time, such as loans, payments, deposits and withdrawals.and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper